Microwave absorbent properties of nanosized cobalt ferrite powders prepared by coprecipitation and subjected to different thermal treatments - FANNIN, PAUL; COUPER, COLIN STUART (Elsevier, 2011)
Cobalt ferrite nanopowders were produced by means of two methods using a common precipitating agent. After precipitation, in the first method the cobalt ferrite was calcined, whilst in the second method the precipitation was followed by a hydrothermal treatment. Characterization of the obtained powders was achieved by X-ray diffraction and scanning electron microscopy / energy dispersive X-ray analysis. Frequency dependence of the complex dielectric permittivity and complex magnetic permeability, over the frequency range 0.1 GHz to 6 GHz, was also studied. By means of the above mentioned investigations, the structure, morphology and microwave absorbent properties of the powders obtained by both methods were compared.
PUBLISHED
Keywords: Condensed matter physics; Cobalt ferrite nanopowders